New insights on cellular structures strengthening mechanisms and thermal stability of an austenitic stainless steel fabricated by laser powder-bed-fusion. (15th January 2021) - Voisin, Thomas; Forien, Jean-Baptiste; Perron, Aurelien; Aubry, Sylvie; Bertin, Nicolas; Samanta, Amit; Baker, Alexander; Wang, Y. Morris
Abstract: Rapid solidification cellular structures are known to play a crucial role in helping achieve high strength and high ductility in 316L austenitic stainless steels fabricated by laser powder-bed-fusion (L-PBF). Despite this, the understanding of their intrinsic characteristics (e.g., crystallographic orientations, dislocations, precipitates, elemental segregations) and the respective impacts on the material's strength and thermal stability remains nebulous. We conduct several dedicated transmission electron microscopy (TEM) studies to investigate these strengthening mechanisms and identified that cell walls follow specific crystallographic orientations. The high density of tangled dislocations inside cell walls are found to have a higher tendency to dissociate, forming wider stacking faults while oxide precipitates are confined inside cell walls. These features act as barriers to moving dislocations upon plastic deformation and contribute to the high strength. Our dislocation dynamic simulations indicate that segregated particles are effective in blocking dislocations locally, helping the formation of dislocation cells and participating to the material strengthening. To study the thermal stability of L-PBF 316L SS, we perform systematic post-processing heat treatments from 400-1200°C. Microstructure characterizations using electron backscatter diffraction, TEM, and synchrotron X-ray diffraction coupled with dislocation dynamics and CALPHAD simulations and tensile testing reveal three heat treatment zones where the structure-property relationship can be tuned. After annealing up to 600°C, the microstructure remains stable; but the work hardening behavior is altered with a material that retains high strength and high ductility. Annealing between 600-1000°C activates elemental diffusion and gradual disappearance of cell walls, leading to a sharp drop in yield strength and a tradeoff between strength and ductility. Low-angle grain boundaries remain stable up to 1000°C while the average grain size defined by high angle grain boundaries is near constant at annealing temperatures up to 800°C. Annealing above 1100°C removes all L-PBF microstructure footprints and renders a conventional-like microstructure. Compared to conventional materials, L-PBF 316LSS displays substantially higher thermal stability and superior performance at elevated temperatures. Graphical abstracts: Image, graphical abstract